Los juegos tradicionales como estrategia para el Desarrollo Socioemocional de los niños de Educación Inicial - Sandoval Sandoval, Julissa Elizabeth (2022)
Identified the problem and the consequences that confinement due to COVID-19 has left on children, such as changes in attitude, negative emotions, lack of interaction with other children of their age and little participation in group games; For this reason, this research aims to create a strategic guide with traditional games for socio-emotional development in children of the Semillitas Initial Education Center "César Francisco Naranjo Rumazo". The proposal aims to get children out of their sedentary routine and poor social relationship, which affected their socioemotional development. A guide was made with ten traditional games with innovative changes in order for the activity to be of greater contribution on the emotional level. The approach used is the constructivist since Piaget and Vygotsky tell us that the child learns by playing and sharing with the environment that surrounds him, children learn better when they work as a team with others, thus reaching significant learning. Finally, the validation of the guide was carried out by two experts and two users who value the guide as a tool that meets the objectives for which it was designed. It is necessary to mention that in this guide the teacher plays a leading role, whose role is characterized by guiding, the teacher will assume a discreet and observant attitude to create a relaxed and fun climate, accepting the mistakes that children make as something normal within development. of the game